A Descriptive Cross-sectional Study on Profile and Outcome of Alcoholic Patient Admitted in the Intensive Care Unit. - Keyal, Niraj Kumar; Sah, Sanjay Kumar; Gupta, Madhu; Ansari, MD Safroz; Yadav, Raj Kishor Prasad; Barnawal, Prakash Kumar (Med Phoenix, 2024)
Introduction: Alcohol consumption is a major public health problem, one of the four major risk factors for non-communicable diseases. This study was conducted to know profile, pattern of alcohol use and outcome of alcoholic patients in the intensive care unit. Materials and Methods: This descriptive cross-sectional study was done in 246 patients of age ≥18 years with a history of alcohol intake admitted in a level three intensive care unit of medical college for more than 24 hours for one year. All the patients admitted to the Intensive Care Unit for 1 year were our sample size. The outcome of the patient was defined as death, and discharge to ward. All data was transferred to the excel sheet and transferred to a Statistical Package for the Social Sciences-16. Results: Two hundred and forty-six patients were included in this study. 194 (78.9%) were males and 52 (21.1%) were females. The current drinker 153 (62.1%), daily 90 (36.5%) drinkers and the combination 69 (28%) of the alcoholic products were more common in this study. 211 (85.7%) and 35 (14.2%) were chronic and acute alcoholic, respectively. Mortality was 40 (16.3%).The mortality in the intubated patient was 22 (29.7%). The duration of delirium, mechanical ventilation, and length of stay was 3.94 ± 3.07, 3.1 ± 1.9, and 5.04 ± 4.8 days, respectively. The dose and duration of lorazepam, midazolam, quetiapine, and haloperidol were 29.96 ± 29.93, 23.27±17.21, 255.3 ± 214.28, 27 ± 25.8 mg, and 3.8 ± 2.81, 3.6 ± 1.7, 3.27 ± 1.92, 2.8 ± 1.03 days, respectively. Conclusion: Alcohol consumption causes increase in mortality, duration of delirium, mechanical ventilation and length of stay in the intensive care unit.